2021
DOI: 10.3389/fmed.2021.731593
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Adverse Reactions to an Inactivated SARS-CoV-2 Vaccine Among Medical Staff in China

Abstract: Objective: We investigated whether there were sex differences in adverse reactions to an inactivated SARS-CoV-2 vaccine among medical staff in China.Methods: From 24 February to 7 March 2021 an online cross-sectional survey was conducted with a self-administered COVID-19 vaccine questionnaire among medical staff in Taizhou, China. In total, 1397 interviewees (1,107 women and 290 men) participated in the survey.Results: In our study, 178 (16.1%) women and 23 (7.9%) men reported adverse reactions following their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…This is not surprising, since it was well-known, even before the COVID-19 pandemic, that biological sex differences could influence the vaccine uptake, responses, and outcome [ 89 ]. Recent studies showed that the side effects of the Pfizer-BioNTech [ 87 , 90 , 91 ], AstraZeneca [ 90 , 91 , 92 ], Sinopharm [ 12 ], Sputnik V [ 11 ], SinoVac [ 91 , 93 ], Johnson & Johnson and Moderna [ 90 ] vaccines were significantly more frequent in females. With a view to reducing post-vaccination side effects in females and increasing immunogenicity in males, Ciarambino et al [ 94 ] recommended that the vaccine development should be sex-specific, and that sex-related variables should be examined in pre-clinical and clinical vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, since it was well-known, even before the COVID-19 pandemic, that biological sex differences could influence the vaccine uptake, responses, and outcome [ 89 ]. Recent studies showed that the side effects of the Pfizer-BioNTech [ 87 , 90 , 91 ], AstraZeneca [ 90 , 91 , 92 ], Sinopharm [ 12 ], Sputnik V [ 11 ], SinoVac [ 91 , 93 ], Johnson & Johnson and Moderna [ 90 ] vaccines were significantly more frequent in females. With a view to reducing post-vaccination side effects in females and increasing immunogenicity in males, Ciarambino et al [ 94 ] recommended that the vaccine development should be sex-specific, and that sex-related variables should be examined in pre-clinical and clinical vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chinese men have higher prevalence of obesity than women, 65,66 which has been reported to lead to decreased pain sensitivity 67,68 . To date, sex has not yet emerged as a biological variable evident in the disaggregation of data and analyses in most studies on COVID‐19 vaccines, with only limited studies reporting adverse events by it 44,69,70 . Previous study revealed whole‐virus trivalent inactivated influenza vaccine could induce higher levels of IgM as well as H1N1‐specific IgG1 responses in female mice compared to male mice 71 .…”
Section: Discussionmentioning
confidence: 99%
“…has not yet emerged as a biological variable evident in the vaccines, with only limited studies reporting adverse events by it. 44,69,70 Previous study revealed whole-virus trivalent inactivated influenza vaccine could induce higher levels of IgM as well as H1N1-specific IgG1 responses in female mice compared to male mice. 71 More interestingly, antibody responses among women given a half dose of trivalent inactivated vaccine were similar to or greater in magnitude when compared with responses among men given a full dose.…”
Section: Discussionmentioning
confidence: 99%
“…vaccine is also inconclusive in other individuals without psoriasis. [28][29][30][31] A systematic review on the 75 clinical trials on different types of COVID-19 vaccines in 2021 showed no statistically significant differences in vaccine efficacy and adverse events between women and men among 7 interventional studies. 29 Some mechanisms have been described to explain why women may be at higher risks for developing adverse events.…”
Section: Ta B L E 1 Demographic Data Between Patients With and Withou...mentioning
confidence: 99%